The work of the nursing team in the operating room and the health-related damages - Bruna Pires Madrid; Cecília Helena Glanzner (Universidade Federal do Rio Grande do Sul, 2021)
ABSTRACT Objectives: to analyze the work of the nursing team in the operating room and the physical, psychological, and social damage related to occupational health. Methods: quantitative study conducted from November 2017 to January 2018 in the operating room of a university hospital. The sample consisted of 160 nursing workers who responded to the Work-Related Damage Assessment Scale. Data were analyzed using the Student's t test, One-Way analysis of variance (ANOVA) followed by Pearson's chi-square test. Results: psychological and social damage were assessed by workers as low risk by 86.8% (139) and 87.4% (140), respectively. Physical damage was considered a medium risk by 57.9% (93) of the sample. Conclusions: the results direct the attention of managers and the occupational medicine service to physical damage, preventing them from getting worse and thus promoting improvements in working conditions and occupational health.